Book Review: "The History of the Body in Literature" by Seyyed Mehdi Zarqani - hamed tavakoli darestani (تاریخ ادبیات)
The Book of Body History in Literature, by Seyyed Mehdi Zarghani et al. (1398), deals with the development of different bodies and their classification in the history of Persian literature and their different views. Examines the body in the works of poets, mystics, and artists. From the point of view of the present, the present book is very novel and novel, but given its newness and lack of detailed research background, it inevitably suffers from some "content" and "structural" slips and defects. That's right. Since this work may be cited and used by other scholars, mentioning the book's slips is necessary. The present article, therefore, is based on a thought-provoking, far-fetched judgment, in order to "revise" and "refine" some of the issues in the book by reflection, reflection, and discussion. Book slides can include: Methodological errors, Contradition, Reduction, Weak theoretical framework, One-dimensional (ideological) view, Lack of some important resources, He noted the lack of coherence and fragmentation in the aims of the research and so on. In the present article, we will explain and critique some of these points and their critiques.